Mecanismos de apoio oferecidos pelas incubadoras e sua relação com os critérios de sucesso da graduação das empresas incubadas - Schwingel, Ângela Watte (2023)
This study aimed to analyze which support mechanisms are offered by the incubators of companies associated with ANPROTEC, which are related to the success criteria for the graduation of their incubatee companies. Therefore, the applied methodology was classified as descriptive and quantitative, employing a survey with data collection through the application of a questionnaire with 79 managers of companies graduated from Brazilian incubators. The analysis of the data was carried out through the Partial Least Squares Structural Equation Modeling (PLS-SEM) tests. The study showed that there is a strong correlation between all eleven support mechanisms raised with all eight evaluation criteria of graduation success, in addition to identifying that the physical and human resources offered by incubators are the support mechanisms that least influence the success of companies that have gone through the incubation process. Based on this study, it can be stated that there is not only one support mechanism that can influence the success of an incubation program, but rather the relation between different mechanisms and the success evaluation criteria adopted by each of the incubators that help incubated companies and incubators to visualize which are the mechanisms that most impact the improvement of the incubation process.